Impact of dynamic factors on the exchange flow between two neighboring bays with contrasting topography during summer: A numerical study - Kwak, Myeong-Taek; Cho, Yang-Ki (Frontiers in Marine Science, 2023)
A high-resolution, three-dimensional numerical ocean model was employed to understand the exchange flow through Noryang Channel, which connects Gwangyang Bay and Jinju Bay. These two bays exhibit contrasting topographies, with Gwangyang Bay connected to the open ocean through a broad and deep channel, whereas Jinju Bay is relatively isolated from the open ocean by a narrow and shallow channel. Numerical experiments were conducted to determine the contribution of river discharge, wind stress, surface heat flux, and tides to the exchange flow between the two bays during summer. The results suggested that river discharge was the dominant factor affecting the exchange flow along Noryang Channel. Particularly, a high river discharge during summer increased the sea level in Jinju Bay, creating a barotropic flow toward Gwangyang Bay. However, the dense water entering Gwangyang Bay through the wide and deep channel generated a baroclinic flow toward Jinju Bay along the lower layer of Noryang Channel. An analytical model supported the conclusion that river discharge is the main driver of the exchange flow in Noryang Channel.